A CuII‐Salicylidene Glycinato Complex for the Selective Fluorometric Detection of Homocysteine over 20 Proteinogenic Amino Acids. Issue 6 (20th June 2022) - Li, Xuecong; Yadav, Prerna; Spingler, Bernhard; Zelder, Felix
Abstract: Homocysteine (Hcy) is a sulfur‐containing α‐amino acid that differs by one methylene (CH2 ) subunit from homologous cysteine (Cys). Elevated levels of Hcy are diagnostic markers of cardiovascular disease and other medical conditions. We present a new Cu II ‐salicylidene glycinato complex 1 for the selective fluorometric detection of Hcy in water. In the presence of this analyte, the non‐fluorescent copper‐complex demetallates and disassembles into its building blocks. This process liberates a 3‐chloro‐5‐sulfosalicylaldehyde signaling unit and is accompanied by a 51‐fold turn‐on fluorescence at 485 nm (λex =350 nm). Out of twenty proteinogenic amino acids, only histidine (12‐fold turn‐on fluorescence) and Cys (8‐fold turn‐on fluorescence) trigger some disassembly of probe 1 . In comparison with important pioneering work on the detection of biothiols, this study strikingly demonstrates that structural modifications of chelate core structures steer substrate selectivity of metal‐based probes. Importantly, probe 1 has proven suitable for the detection of Hcy in artificial urine. Abstract : A new Cu II ‐salicylidene glycinato complex for the selective fluorometric detection of homocysteine (Hcy) over 20 proteinogenic amino acids in water, following a disassembly approach, is presented. This probe allows for detection of Hcy in artificial urine.